2007
DOI: 10.2215/cjn.01470506
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Excretion of Urinary Podocytes Reflects Disease Progression in IgA Nephropathy and Scho[Combining Diaeresis]nlein-Henoch Purpura Nephritis

Abstract: Recent studies have revealed that podocytopenia leads to glomerular scarring and that the loss of podocytes into the urine may be a cause of podocytopenia. The purpose of this study was to examine whether serial examinations of urinary podocytes (u-podo) could be a useful predictor of disease progression in children with glomerulonephritis. Urine samples and renal biopsy specimens from 20 patients (10 males and 10 females; mean age 11.8 yr; range 4 to 24 yr) with IgA nephropathy (n ‫؍‬ 17) and Henoch-Schö nlei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 29 publications
7
81
0
3
Order By: Relevance
“…16 As a result of its localization throughout the cell body, PDX remains well preserved in many glomerulopathies independent of the integrity of the slit diaphragm. PDX has played a key role in detecting podocyte excretion in many different renal diseases [i.e., membranous nephropathy (MN), membranoproliferative glomerulonephritis, focal segmental glomerulosclerosis (FSGS), immunoglobulin A (IgA) nephropathy (IgAN), Henoch-Schönlein purpura nephritis (HSPN), 17 lupus nephritis (LN), diabetic nephropathy (DN), 18 and preeclampsia 19 ]. Several studies have also indicated that the number of PDX-positive cells in the urine falls after various therapeutic interventions in patients with FSGS, LN, HSP, IgAN, PSGN, and DN.…”
Section: Function Of Podocytes In Kidney Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 As a result of its localization throughout the cell body, PDX remains well preserved in many glomerulopathies independent of the integrity of the slit diaphragm. PDX has played a key role in detecting podocyte excretion in many different renal diseases [i.e., membranous nephropathy (MN), membranoproliferative glomerulonephritis, focal segmental glomerulosclerosis (FSGS), immunoglobulin A (IgA) nephropathy (IgAN), Henoch-Schönlein purpura nephritis (HSPN), 17 lupus nephritis (LN), diabetic nephropathy (DN), 18 and preeclampsia 19 ]. Several studies have also indicated that the number of PDX-positive cells in the urine falls after various therapeutic interventions in patients with FSGS, LN, HSP, IgAN, PSGN, and DN.…”
Section: Function Of Podocytes In Kidney Diseasesmentioning
confidence: 99%
“…In contrast, there was no significant correlation between urinary studies and any of the renal chronicity scores. A prospective study by Hara et al 17 examined patients with HSPN and showed a strong correlation between the cumulative burden of the excretion of PDX-positive cells (the amount excreted in 6 consecutive months) and the development of GS in follow-up biopsies. The number of podocytes in the urine was found to be clinically useful as a diagnostic tool for glomerular versus nonglomerular diseases, inflammatory versus noninflammatory diseases, and as a marker for the severity of active glomerular injury.…”
Section: Henoch-schönlein Purpura Nephritismentioning
confidence: 99%
“…[1][2][3] Podocyturia has been identified before the onset of proteinuria in diseases such as diabetes, focal segmental glomerulosclerosis, IgA nephropathy and lupus nephritis. [4][5][6][7] Under certain conditions, apoptosis of the podocytes has been observed along with consequent detachment into the urinary space, thus leading to podocyturia and podocytopenia. Moreover, the intensity of this phenomenon has been related to the prognosis of kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…In an animal model with chronic glomerulopathy, increased and persistent urinary excretion of podocytes correlates with the progression of the disease. 42 Moreover, recent studies have shown that corticosteroid treatment may have direct effects on podocytes. 43,44 In contrast, the clinical response to immunosuppression therapy in focal segmental glomerular sclerosis is different according to the podocyte number.…”
Section: Discussionmentioning
confidence: 99%